Deconstructing the Sykes-Picot Myth: Frontiers, Boundaries, Borders and the Evolution of Ottoman Territoriality - KURŞUN, ALİ MURAT (My University, 2020)
This study aims to evaluate the emergence of the Sykes-Picot order and deconstruct its mythologization by proposing an evolutionary assessment of border understanding. This study addresses the following primary research questions: How did the interplay of domestic, regional, and international developments lay the groundwork for the formation of the Sykes-Picot territorial order? How was the administrative structure and regional divisions before the Sykes-Picot agreement and to which border categorizations did these structures correspond? Was the Sykes-Picot agreement the only international intervention that affected the borders of the region or were there other international interventions before the Sykes-Picot agreement? This study argues that the history of Middle Eastern border formation is not only an international one but also involves many aspects that have not widely been taken into consideration. In doing so, this paper adopts a critical historical perspective to analyze the evolution of Middle Eastern borders. This paper proposes a three-tracked evolutionary analytical framework (frontiers, boundaries, borders) to analyze the emergence of borders and applies it to the emergence of Ottoman territoriality. This study concludes that the Sykes-Picot agreement is only one, complementary part of a long process in the emergence of Middle Eastern geopolitics. Keywords: Ottoman territoriality, Sykes-Picot Agreement, Middle Eastern borders, border studies
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Uluslararası İlişkiler; Social Sciences and Humanities; Political Science; International Relations; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; ULUSLARARASI İLİŞKİLER; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; INTERNATIONAL RELATIONS; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities; Ottoman territoriality; Sykes-Picot Agreement; Middle Eastern borders; border studies